Hijacking Subaltern"s history (broken bodies, broken voices): Decolonial critique of "Subaltern whiteness" in South Africa - Kaunda, Chammah J. (HTS teologiese studies, 2017)
This article uses decolonial to critique the discourse of ‘subaltern whiteness’ by questioning some Afrikaner scholars’ morality of regarding ‘white Afrikaners as subaltern’. Subaltern designates submerged, subordinated, exploited or suppressed – those whose voices have been historically muted, their humanity stripped by those with sociopolitical and economic power. Within South Africa, this raises the question: to what extent can white Afrikaners be regarded as subaltern? The article proposes indivisibility of epistemic vulnerability and regenerative theological praxis both emerging within Afrikaner theological discussion as viable response to broken bodies of those who still bear the marks or scars of apartheid and rather not to seek to hijack their voice.